The state of the State in Geography : A Review Essay - Bradbury, John (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1980)
In the past recent years, some economic and political geographers have focused their attention upon the role of the state in the capitalist society. In this article, the author makes a historical review of the main contributions of geographers as to this aspect, he presents the most recent developments of the theory of state stemming from other disciplines, and he proposes four possible ways of interpreting the function of the state in a developed society: that is, the relations of state to circuits of capital, to corporations, to capital and classes and, finally, to fiscal policies.